2001
DOI: 10.1103/physrevb.63.205426
|View full text |Cite
|
Sign up to set email alerts
|

Ab initiostudy ofBaTiO3andPbTiO3surfaces in external ele

Abstract: For the ferroelectric perovskite compounds BaTiO3 and PbTiO3, we have studied the effects of external electric fields on the structural properties of the (001) surfaces. The field-induced changes in the surface interlayer spacings and bucklings have been calculated using a first-principles ultrasoftpseudopotential approach, and the change of the polarization and the ferroelectric distortions in the surface layers have been obtained. The surfaces are represented by periodically repeated slabs, and an external d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
251
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 335 publications
(261 citation statements)
references
References 23 publications
9
251
0
1
Order By: Relevance
“…A value of c/2 = 2.018Å was used to obtain η and d ij . 10,12,19 The rumpling for P ± states has the same sign as the polarization and is quantitatively similar for the three XPD patterns. The rumpling magnitude varies between 0.01 and 0.06Å with a mean value of 0.028Å (0.70% of the lattice parameter), whereas the magnitude of the interlayer relaxation varies between 0.01 and 0.13Å with a mean value of 0.038Å (0.95% of the lattice parameter) over the first four layers.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…A value of c/2 = 2.018Å was used to obtain η and d ij . 10,12,19 The rumpling for P ± states has the same sign as the polarization and is quantitatively similar for the three XPD patterns. The rumpling magnitude varies between 0.01 and 0.06Å with a mean value of 0.028Å (0.70% of the lattice parameter), whereas the magnitude of the interlayer relaxation varies between 0.01 and 0.13Å with a mean value of 0.038Å (0.95% of the lattice parameter) over the first four layers.…”
Section: Discussionsupporting
confidence: 49%
“…Surface structural modifications have been the subject of theoretical studies. [10][11][12] Following Meyer and Vanderbilt, 12 relaxation is given by the average atomic displacement β = [δ z (M) + δ z (O)] /2, where δ z (M) and δ z (O) are the displacements of the Ba or Ti ions and the oxygen ions, respectively, from the bulk positions. The change in the interlayer spacing d ij is the difference in the average atomic displacements for two adjacent layers β i and β j .…”
Section: Introductionmentioning
confidence: 99%
“…9 This idea has been corroborated by ab initio calculations carried out on perovskite films, which tell that no critical thickness exists for polarization parallel to the surface 10 and that polarization perpendicular to the surface can exist in films three unit-cells thick if the depolarization field is artificially removed. 11,12 On the other hand, it has been found that the depolarization field plays a dominant role in reducing polarization normal to the surface and depressing ferroelectric transition temperatures in thin films. In a continuum model by Batra et al 4 which includes the depolarization effect, a critical thickness of 100Å for perovskite films was analytically derived, assuming a Thomas-Fermi screening length of 1Å for the metal electrodes.…”
mentioning
confidence: 99%
“…This observation is in agreement with previous DFT calculations with external fields. 12 In going from m=2 to m=4, both P and c/a decrease towards the bulk values as the surface-tovolume ratio decreases and the surface effect is averaged over more layers. To further check whether there exists a thickness limit below which ferroelectricity disappears in this system, we examine the structure at m = 1.…”
mentioning
confidence: 99%
“…In particular, "nanoscale" ferroelectrics have attracted considerable attention [1,2,3,4,5]. The question of the existence of a critical thickness, in other words whether or not ferroelectricity can be maintained at reduced dimensions, is amongst the most exciting topics of the field today, with very active experimental [6,7,8,9] and theoretical efforts [10,11,12].…”
Section: Introductionmentioning
confidence: 99%